A Glimpse of Few Diagnostic Laboratory Tests - Umer Saeed Ansari, (Pakistan Journal of Medical & Health Sciences, 2022)
Medical laboratories perform numerous in vitro diagnostic tests for the diagnosis and prognosis of a variety of diseases. There are some well renowned medical laboratories in Pakistan performing a spectrum of advanced diagnostic tests. This editorial provides a glimpse of few advanced laboratory tests with diagnostic significance Calprotectin (detected in stools): Calprotectin is a protein released by neutrophils, & its presence in the stool is indicative of inflammation in the intestines; its detection also enables to distinguish between inflammatory bowel disease & non-inflammatory bowel conditions, thus also estimated to monitor Ischemic Bowel Disease (IBD) activity, or Irritable bowel syndrome (IBS).